A Systemic Functional Study on the Conversational Structure of an Indonesian Spontaneous Dialogue - Susanto Susanto (University of Kuningan, 2015)
Spontaneous dialogue is an example of spoken text in which its potential can be observed through its conversational structure. As an attempt to interpret the language in spoken text, the paper investigates a spontaneous dialogue in Bahasa Indonesia (Indonesian). The discussion focuses on its conversational structure within systemic functional framework. The structure is built up in the semantic stratum by looking at its exchange and commodity for its speech function. The exchanges are realized by Initiate/Respond moves and the commodity could be either Knowledge or Action oriented. Since a spontaneous dialogue is a contextual phenomenon in experiencing language use, the finding of conversational structure can bring further discussion on connections among individuals bearing cultural identities realized by their experiences through languages.Keywords: conversational structure, exchange, commodity, systemic functional linguistics.